2008
DOI: 10.1007/s00122-008-0841-0
|View full text |Cite
|
Sign up to set email alerts
|

SSRs and INDELs mined from the sunflower EST database: abundance, polymorphisms, and cross-taxa utility

Abstract: Simple sequence repeats (SSRs) are abundant and frequently highly polymorphic in transcribed sequences and widely targeted for marker development in eukaryotes. Sunflower (Helianthus annuus) transcript assemblies were built and mined to identify SSRs and insertions-deletions (INDELs) for marker development, comparative mapping, and other genomics applications in sunflower. We describe the spectrum and frequency of SSRs identified in the sunflower EST database, a catalog of 16,643 EST-SSRs, a collection of 484 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(86 citation statements)
references
References 62 publications
6
76
0
2
Order By: Relevance
“…Until now, only Tang et al (2002) reported the sequence information amplified by primers ORS759, ORS838, ORS840, ORS1112, and only one fragment was achieved by each of the primers. By comparing the alignment of our results with previous report (Tang et al, 2002), it was found that the homologies of all variation sequences are greater than 92%, or even as high as 99%, indicating the high conservation of genomic sequence of sunflower (Heesacker et al, 2008). Based on the high conservation of the sequences, the analysis of sequence variation showed that deletion, insertion and replacement occurred at some sites in the genomic DNA of sunflower, which was probably the main reason for the major change in morphological characters induced by space flight.…”
Section: Discussionsupporting
confidence: 55%
“…Until now, only Tang et al (2002) reported the sequence information amplified by primers ORS759, ORS838, ORS840, ORS1112, and only one fragment was achieved by each of the primers. By comparing the alignment of our results with previous report (Tang et al, 2002), it was found that the homologies of all variation sequences are greater than 92%, or even as high as 99%, indicating the high conservation of genomic sequence of sunflower (Heesacker et al, 2008). Based on the high conservation of the sequences, the analysis of sequence variation showed that deletion, insertion and replacement occurred at some sites in the genomic DNA of sunflower, which was probably the main reason for the major change in morphological characters induced by space flight.…”
Section: Discussionsupporting
confidence: 55%
“…In addition, Heesacker et al (2008) developed 16,643 EST-SSR markers from common sunflower EST libraries and inquired their transferability to closely and distantly related species of the Compositae family. Even though a low presence of these markers were common to safflower, still, their contribution to dense linkage mapping and drought-tolerant QTLs identification may be beneficial.…”
Section: Gene Mapping and Qtls For Drought Tolerancementioning
confidence: 99%
“…Initial EST library content and methods of library construction, sequencing, and assembly are described in Heesacker et al (2008). Subsequent library construction and sequencing have produced new EST collections for H. ciliaris, H. exilis, and H. tuberosus.…”
Section: Ortholog Identificationmentioning
confidence: 99%